(untitled) (Historia, 2021)
This work is the fifteenth (and final) number to appear in the Vrijstatia series. Despite its value to historians of the Free State, as well as mission historians, this series has never been a financially self-sustaining one. Its editor has always had to rely on subsidies for its publication. With changing publishing priorities accompanying political change in the country since the 1990s, it was impossible to obtain subsidies for volumes...